2019
DOI: 10.1002/bjs.11215
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival after endovascular and open repair of unruptured abdominal aortic aneurysm

Abstract: Background The aim of this study was to examine patterns of 10‐year survival after elective repair of unruptured abdominal aortic aneurysms (AAAs) in different patient groups. Methods Patients having open repair or endovascular aneurysm repair (EVAR) in the English National Health Service between January 2006 and December 2015 were identified from Hospital Episode Statistics data. Postoperative survival among patients of different age and Royal College of Surgeons of England (RCS) modified Charlson co‐morbidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 23 publications
(61 reference statements)
1
21
0
Order By: Relevance
“…A recently published study used HES data to investigate long term outcomes after repair of unruptured AAAs in 37 138 patients and found that rupture rates were higher for EVAR. 29 There was notable variation in the use of EVAR and open surgery between trusts in the present dataset. Differences in presentation, anatomical features, resource availability and patient preference may also play a role here.…”
Section: Discussionmentioning
confidence: 77%
“…A recently published study used HES data to investigate long term outcomes after repair of unruptured AAAs in 37 138 patients and found that rupture rates were higher for EVAR. 29 There was notable variation in the use of EVAR and open surgery between trusts in the present dataset. Differences in presentation, anatomical features, resource availability and patient preference may also play a role here.…”
Section: Discussionmentioning
confidence: 77%
“…These data have recently been corroborated by a large series from the United Kingdom of over 38,000 unruptured AAA repairs collected by the UK Hospital Episode Statistic. 10 EVAR was associated with higher 10-year mortality and higher risk of rupture over 9 years than open surgical repair (3.4% vs 0.9%).…”
mentioning
confidence: 92%
“…Johal et al recently aimed to examine patterns of 10-year survival after elective repair of unruptured AAA and investigated the survival among patients of different age and different co-morbidity score pro les from the English National Health register 25 . The long-term survival patterns after elective open repair and EVAR for unruptured AAA varied markedly across patients with different age and co-morbidity pro les.…”
Section: Association Of Cardio-metabolic Factors With Post-operative mentioning
confidence: 99%